IDENTIFICATION OF BUSINESS ENTERPRISES BUMDES BASED ON SOCIAL AND ECONOMIC ASPECT (Case Study at BUMDes Ijen Lestari Tamansari Village District of Banyuwangi) - Moh. Hudi Setyobakti (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
Law No. 6 of 2014 on Villages, provides an important position for the village to play its role in development. The important role of the village is the local authority possessed by the village in managing its household. Village economy is one of the important factors in assessing the success of village development. The village economic problems need to be solved by handling thoroughly, starting from the construction of infrastructure facilities, to developing the potential of the village to be optimized into opportunities for business opportunities that prosper the village community. Village Owned Enterprises, here in after referred to as BUMDes, become one of the important mandates contained in the Village Law. BUMDes urgency is affirmed in Permendesa number 4 of 2015. The context of BUMDes establishment is expected to be the driving force of the village economy, meaning that the establishment of BUMDes is not merely an orientation to the profit of the institution, but the more essence is the establishment of BUMDes should be able to provide both economic and social benefits to villagers.The type of this research is descriptive qualitative, with the aim to identify and analyze the feasibility aspects of BUMDes business in terms of social and economic aspects. The results showed that BUMDesIjen Lestari Tamansarivillage District of Banyuwangi gave positive impacts economically and socially for the villagers like directly or indirectly. BUMDes's main business sector engaged in tourism management has an impact for residents around Ijen region, in the form of additional income from multiplayer tourism effects. The direct impact of BUMDes employees' involvement in the management of activities and community involvement in BUMDes businesses such as local food producers packed with BUMDes and community-based homestay managers.Keywords: BUMDes, Social Aspect, Economic Aspect, Banyuwangi